The neglect of quantitative research in green criminology and its consequences - Lynch, Michael J. (Critical criminology, 2017)
While interest in green criminology has rapidly expanded over the past twenty-five years, much of this growth has occurred on the periphery of orthodox criminology. This article suggests that green criminology’s marginalization is partially a result of its non-quantitative methodology. We hypothesize that non-quantitative tendencies within green criminology distance it from orthodox criminology because orthodox criminology values quantitative methods (Tewksbury et al. in J Crim Justice Educ 16(2):265-279, 2005). Here, we examine how neglecting quantitative research methods may contribute to inattention to green criminology within orthodox criminology, and we consider what can be done to change that situation. We suggest that employing quantitative approaches within green criminology is one way to increase its appeal to mainstream criminology, and that quantitative studies, in conjunction with other research methodologies, can also enhance generalizability of findings, influence policy, and advance theory construction and hypothesis testing.